2023
DOI: 10.3390/polym15020412
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Bonding and Mechanical Performance of Epoxy Asphalt Bond Coats with Graphene Nanoplatelets

Abstract: Improving bonding and mechanical strengths is important for the application of bond coats used in the construction of steel deck bridges. Graphene nanoplatelets (GNPs) are attractive nanofillers for polymer modification because of their low cost, ultra-high aspect ratio, and extraordinary thermal and mechanical performance. In this paper, GNPs were used to reinforce the epoxy asphalt bond coat (EABC). The morphology, viscosity–time behavior, contact angle, dynamic mechanical properties, and mechanical and bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…The UCS tests reveal intriguing trends in strength development, which can be contextualized based on previous studies. The early-age (2 h) UCS values of CAM mixtures modified with epoxy resin and CRP tend to be slightly lower compared to the control mixture, as similarly reported by Jing et al [17]. Their research highlighted the initial strength reduction associated with epoxy resin-modified mixtures, which was attributed to delayed hydration kinetics.…”
Section: Strength Developmentsupporting
confidence: 75%
See 1 more Smart Citation
“…The UCS tests reveal intriguing trends in strength development, which can be contextualized based on previous studies. The early-age (2 h) UCS values of CAM mixtures modified with epoxy resin and CRP tend to be slightly lower compared to the control mixture, as similarly reported by Jing et al [17]. Their research highlighted the initial strength reduction associated with epoxy resin-modified mixtures, which was attributed to delayed hydration kinetics.…”
Section: Strength Developmentsupporting
confidence: 75%
“…Recently, epoxy resin and crumb rubber powder (CRP) have gained significant attention as valuable additives in asphalt mixtures due to their unique properties and potential benefits [14][15][16]. Epoxy resin, known for its adhesive and cohesive characteristics, has been employed to enhance the bonding between asphalt and aggregate particles, resulting in improved asphalt mix durability [17][18][19]. Similarly, CRP, a recycled material derived from discarded tires, offers benefits such as improved elasticity, reduced rutting, and enhanced resistance to temperature-related distresses when incorporated into asphalt mixtures [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, eight material formulations were selected to investigate the influence of three different mineral fillers on the viscoelastic behavior of a bitumen-free asphalt mixture in its solid state (cured) under application-relevant loadings. The processing of polymerbased bitumen-free asphalt mixtures is also a field of active research, and findings are found in the literature [3][4][5]7,9,10,[22][23][24]. A poly(methyl methacrylate) (PMMA)-based resin was used instead of bitumen, mixed with a thixotropy agent (hydrophilic fumed silica with a specific surface area of 200 m 2 /g), a binder, a catalysator, and a color pigment to improve processability.…”
Section: Methodsmentioning
confidence: 99%
“…Several research studies have been conducted to investigate the viscoelasticity of asphalt mixtures, and guidelines such as the AASHTO, MEPDG, or ASTM specifications define the dynamic mechanical complex modulus tests at selected temperatures and loading frequencies [20]. It is important to point out that the viscoelasticity characterization is not only relevant in the processing but is crucial for the long-term behavior of the cured solid asphalt mixture [21][22][23][24]. Moreover, dynamic mechanical analyses must ideally be performed under tensile, compressive, and shear loading.…”
Section: Resin-based Pavements Provide An Excellent Foundation For Ad...mentioning
confidence: 99%
“…Due to the demand from the economy and environment to properly manage waste, the interest in reusing WEO has increased [11]. Several researchers have looked into the idea of employing WEO to rejuvenate the characteristics of aged asphalt binders [12]. The studies found that adding waste oil to RAP asphalt improved the workability and lowered the mixing temperature.…”
Section: Introductionmentioning
confidence: 99%